2017
DOI: 10.1136/bmjopen-2016-015211
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on prevalence of chronic obstructive pulmonary disease (COPD) in India: rationale and methods

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a common preventable and treatable chronic respiratory disease, which affects 210 million people globally. Global and national guidelines exist for the management of COPD. Although evidence-based, they are inadequate to address the phenotypic and genotypic heterogeneity in India. Co-existence of other chronic respiratory diseases can adversely influence the prognosis of COPD.India has a huge burden of COPD with various risk factors and comorbid conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 28 publications
2
41
0
Order By: Relevance
“…3 The Global Burden of Disease Study revealed that COPD is the fourth leading cause of death worldwide, claimed 3.2 million lives in 2015, 4 and projected to be the third leading cause by 2030. 5 In addition to its impact on mortality, COPD is also associated with an appreciable impact on morbidity and costs. 2,6,[7][8][9] Consequently, it is a high priority area to focus on.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 The Global Burden of Disease Study revealed that COPD is the fourth leading cause of death worldwide, claimed 3.2 million lives in 2015, 4 and projected to be the third leading cause by 2030. 5 In addition to its impact on mortality, COPD is also associated with an appreciable impact on morbidity and costs. 2,6,[7][8][9] Consequently, it is a high priority area to focus on.…”
Section: Introductionmentioning
confidence: 99%
“…11 The lack of perceived benefit from therapy has also been associated with 30% of patients with COPD intentionally discontinuing their therapy. 26 Whilst the exact burden of COPD in India is currently unknown 5 although some studies have suggested prevalence rates of between 6.5% and 7.5% 27 prevalence rates for COPD are known to be appreciably higher in low and middle income countries such as India 2 Overall, China and India appear to account for 66% of global COPD mortality. 5,28 Alongside this appreciable burden, we are aware that there is currently very little published data on the impact of clinical pharmacist-led patient self-management in COPD in India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with chronic cardiac, hepatic, renal, haematological malignancy, endocrine, neurological psychiatric diseases, (as determined by history, physical examination and screening investigations) pregnant and lactating mother, bronchiectasis, fibrosis, TB or significant co-morbidity that might affect lung function, (e.g. poorly controlled heart failure, atrial fibrillation or ischaemic heart disease) regular oxygen or nebulised bronchodilator therapy, respiratory infection, hospitalized within 6 weeks prior to visit and steroidal therapy were excluded from the study 17,18,19,20 . The socio-demographic parameters were assessed.…”
Section: Materials and Methods: Study Designmentioning
confidence: 99%
“…These pollutants not only alter the ecological balance but also degrades the indoor air quality (IAQ) associated with building structures in urban areas [21]. As a result, several health issues like pulmonary and respiratory disorders were observed, and approximately 500,000 cases were reported every year in India [31].…”
Section: Introductionmentioning
confidence: 99%